IMPLICATURE IN WHEN TIME THE STOOL STILL - Mitha Angelika Nababan; Charles David Marudut Silalahi; JW Logita Lezmi (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study explores implicature in the song "When Time Stood Still", analyzing how implied meanings contribute to the song’s overall interpretation. Using Grice’s Cooperative Principle and its maxims, the research identifies conversational and conventional implicatures present in the lyrics. The study examines how language, context, and poetic devices shape the intended and inferred meanings beyond the literal text. The findings reveal how implicature enhances emotional depth, conveys hidden messages, and engages listeners in meaning-making. This research contributes to the understanding of linguistic pragmatics in song lyrics, highlighting the role of implicature in artistic expression.